Social Culture Change Sebagai Eksternalitas Transformasi Digital Di Indonesia - Rena Febrita Sarie; Dwi Lesno Panglipursari; Allen Pranata Putra (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
Changes in social culture on digital transformation in Indonesia have both positive and negative implications. This article presents a new anti-thesis in digital economy thinking, namely changes in people's behavior. The purpose of this study is to determine the socio-cultural changes of society in the digital transformation of eocnomy, the externalities of the digital economy, and the adverse impact of the slow legality of legislation. This research is a qualitative descriptive that uses indepth interviews from several key informants, so as to obtain valid data saturation based on the interviews that have been conducted. The analysis of this study used data triangulation, namely documents, interviews, and observations. The results show that the digital transformation of the economy will always be influenced by externalities, and these externalities can be negative or positive. The stigma of society in this case becomes important to be able to avoid the negative impact of transformation. Often transformation is not accompanied by clear legality of legislation, so legality in Indonesia seems slow to adapt to social and economic changes. Legality is based on events, but when an event has grown and harmed many societies, then the legality is formed. There will always be a fee to be paid to exchange the slow legality of the legislation.Keywords: Social Culture, Externalities, Digital Economy